Phytochemical profiling and bioactive potential of bael gum using UHPLC-Q-TOF-MS: a novel nutraceutical source - Jha, Suchisree; Yadav, Ashok; Gupta, Saran Kumar; Ram, Asha; Choudhary, Girija; Garg, Sandeep; Anuragi, Hirdayesh; Yadav, Ronak; Sandeep, Guntukogula Pattabhi; Sonwalkar, Prasad Manikrao; Kumar, Naresh; Dev, Inder (Frontiers in Nutrition, 2025)
IntroductionPlant gums are recognized for their notable nutraceutical and medicinal properties. Numerous studies have explored the medicinal potential of Aegle marmelos, particularly leaves, fruits, and seeds. Its hardy nature, drought tolerance, and diverse applications make it a promising climate-smart crop for agroforestry systems.MethodsThe present study was therefore designed to address this limitation by conducting an in-depth phytochemical and nutraceutical profiling of bael gum and evaluating different parameters, i.e., macroscopic parameters, physical parameters, antioxidant enzyme activities, total phenol content, antioxidant analysis (DPPH assay, metal chelating activity, and ABTS assay). Ultra-high Performance Liquid Chromatography coupled with Quadrupole Time-of-Flight Mass Spectrometry (UHPLC-QTOF-MS) was used to identify a diverse range of bioactive compounds with potential health benefits.ResultsThis study presents a detailed nutritional and phytochemical characterization of bael gum, revealing high levels of total polysaccharides (40.94%), total protein (16.2%), total nitrogen (2.59%), and total amino acids (16.14%). The antioxidant assays demonstrated significant activity with IC₅₀ values of 765.7 ± 1.5 mg/g for metal chelation, 488 ± 1 mg/g for DPPH, and 368.7 ± 0.9 mg/g for ABTS, alongside of total phenol content of 90 ± 1 μg/g FWT.ConclusionThese findings revealed that bael gum is a valuable source of bioactive compounds with promising therapeutic potential and its applicability across multiple industries, including food and beverage, pharmaceutical, cosmetic, and personal care, as well as biodegradable films and edible packaging materials. Furthermore, investigating the mechanisms of action of individual bioactive constituents and evaluating their effectiveness in functional food and therapeutic formulations will be essential to enhance the practical utilization of bael gum.